2022
DOI: 10.1101/2022.02.07.479382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pitfalls of machine learning models for protein-protein interactions

Abstract: Protein-protein interactions (PPIs) are essential to understanding biological pathways as well as their roles in development and disease. Computational tools have been successful at predicting PPIs in silico, but the lack of consistent and reliable frameworks for this task has led to network models that are difficult to compare and, overall, a low level of trust in the PPI predictions. To better understand the underlying mechanisms that underpin these models, we designed B4PPI, an open-source framework for ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…Some authors already do this voluntarily (for example, refs. [54][55][56][57][58][59], mostly in bioinformatics and machine learning so far, but there is potential to expand it to other areas of computational science. In some instances, showing that a new tool is greener can be an argument in support of a new method 60 .…”
Section: Governance and Responsibilitymentioning
confidence: 99%
“…Some authors already do this voluntarily (for example, refs. [54][55][56][57][58][59], mostly in bioinformatics and machine learning so far, but there is potential to expand it to other areas of computational science. In some instances, showing that a new tool is greener can be an argument in support of a new method 60 .…”
Section: Governance and Responsibilitymentioning
confidence: 99%
“…This approach has already been taken by researchers in compute-heavy fields (e.g., Lannelongue & Inouye, 2023b;Xu et al, 2023), and a comprehensive framework for reporting these figures is provided by the Scientific CO 2 nduct initiative ( Sweke et al, 2022; https://scientific -conduct . github .…”
Section: Track Your Emissionsmentioning
confidence: 99%
“…While earlier tools tended to rely on low-power machine learning algorithms, most methods now leverage deep learning and involve longer training times. A recent comparison of machine learning (randomforest)and deep learning(recurrentneu-ral networks) found that in some situations, the deep learning approach could emit 22,000 more GHGs for similar performance (Lannelongue and Inouye 2022). However, runtimes remain small and, in this case, training the deep learning model once had a carbon footprint of 356 gCO 2 e and ∼36 kgCO 2 e (75 kWh) when including fine-tuning the network.…”
Section: Protein-protein Interactionsmentioning
confidence: 99%